PREVALENCE OF URINARY TRACT INFECTIONS AMONG FEMALES OF REPRODUCTIVE AGE GROUP IN TERTIARY CARE TEACHING HOSPITAL - PRASAD RAO M; SREEDEVI K; SRIKANTH A; DIVYA DHARSHINI B (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The purpose of the current study is to isolate, characterize, and evaluate the antibiotic susceptibility profile of the pathogenic bacteria causing urinary tract infections (UTIs) in females of reproductive age. Methods: This is a cross-sectional descriptive study carried out in a Tertiary care teaching hospital for 1 year. A total of 100 urine samples from female patients in the reproductive age range of 15–44 years constitute the study’s sample size. Clean catch midstream urine samples were taken in sterile containers and inoculated on a different culture medium, such as cysteine, lactose, and electrolyte-deficient agar, to isolate the UTI pathogen. MacConkey agar was inoculated in parallel to target the growth of Gram-negative bacilli. Thereafter, using the common microbiological procedures, all positive cultures with significant bacteriuria were identified at the species level based on the colony features, Gram-staining reaction, and pattern of biochemical profiles. To investigate the pattern of antibiotic susceptibility, the disc diffusion method was used. Results: Among the 100 study cases, the prevalence of UTI was seen in 38% of individuals and UTI was absent in 62% of individuals. Among the females (38% cases) who had UTI, 81% had symptomatic UTI and 19% had asymptomatic UTI. Among the 81% symptomatic individuals of UTI, all they showed burning micturition followed by 74% of individuals showed dysuria Among the uropathogens isolated, majority were Escherichia coli (40.7%) followed by CONS (22.3%) Majority of the E. coli isolates showed sensitivity to piperacillin/tazobactam and nitrofurantoin. Conclusion: If left untreated, UTI is a significant public health issue. Early detection and timely treatment will lower the risk of developing further UTI complications, as well as the patient’s pain, length of stay in the hospital, and economic loss.